Renal replacement therapy in neonates with an inborn error of metabolism - Heeyeon Cho (Korean Pediatric Society, 2019)
Hyperammonemia can be caused by several genetic inborn errors of metabolism including urea cycle defects, organic acidemias, fatty acid oxidation defects, and certain disorders of amino acid metabolism. High levels of ammonia are extremely neurotoxic, leading to astrocyte swelling, brain edema, coma, severe disability, and even death. Thus, emergency treatment for hyperammonemia must be initiated before a precise diagnosis is established. In neonates with hyperammonemia caused by an inborn error of metabolism, a few studies have suggested that peritoneal dialysis, intermittent hemodialysis, and continuous renal replacement therapy (RRT) are effective modalities for decreasing the plasma level of ammonia. In this review, we discuss the current literature related to the use of RRT for treating neonates with hyperammonemia caused by an inborn error of metabolism, including optimal prescriptions, prognosis, and outcomes. We also review the literature on new technologies and instrumentation for RRT in neonates